Activity of Counterintelligence Agencies in the State Information Security System: NATO Countries’ Experience and Ukrainian Realities - Kovalenko, E. V.; Pletnov, O. V. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the features of introduction of experience of the NATO countries into the practice of the Ukrainian secret service bodies in the state system of ensuring information security are investigated in the article. In particular, the features of ensuring information security in NATO are analyzed. An assessment of the regulatory base of Ukraine on ensuring cyber security in the context of counteraction to hybrid war is carried out. The prospects of reform of Security Service of Ukraine according to the NATO standards are defined.